Inovasi Produk: Pelatihan Diversifikasi Olahan Makanan Berbasis Fermentasi di Institut Kemahiran Islam Malaysia Sarawak - Hanum Mukti Rahayu; Mahwar Qurbaniah; Linda Lostari (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2025)
Telaga Air Village in Kuching, Sarawak, possesses abundant fisheries and aquaculture resources. The Institut Kemahiran Islam Malaysia Sarawak (IKMAS), as a center for education and community engagement, can foster students’ entrepreneurial spirit by leveraging these local potentials. One concrete effort is providing training in the diversification of fermented food products. This program included the introduction of fish-based fermented products, practical training in fermented sambal production, packaging techniques, sterilization, and evaluation through participant response surveys. Results showed that 100% of participants had never attended similar training. About 83% found the material new and insightful, 72.5% considered it easy to replicate, and 87.5% rated the material delivery as clear. Additionally, 87.5% appreciated the accessibility of the venue, and the organizing committee received a 90% satisfaction rating. Overall, the average participant satisfaction level was 83.75%, categorized as excellent.